2014
DOI: 10.5603/ait.2014.0055
|View full text |Cite
|
Sign up to set email alerts
|

Ten good reasons why everybody can and should perform cardiac ultrasound in the ICU

Abstract: Critical care ultrasonography (CCUS) has been defined as an ultrasound evaluation of the heart, abdomen, pleura and lungs at the bedside by the intensivist, 24/7. Within CCUS, critical care echocardiography (CCE) is used to assess cardiac function and more generally haemodynamics. Experts in haemodynamics have published a 'consensus of 16' regarding an update on haemodynamic monitoring. They reported the ten key properties of an 'ideal' haemodynamic monitoring system, which perfectly match the ten good reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
7
0
4
Order By: Relevance
“…This study has demonstrated that it is feasible to complete the CCUS exam on ICU admission with in a short period (less than 30 minutes) to add more valuable information about the patient besides clinical characteristics, lab work, and other imaging exams. In the consideration of properties of noninvasive, responsible, rapid, affordable and reproducible data collecting at the bedside and providing specific data that may not be obtained from other diagnostic methods[ 33 ], we believe it is precious to encourage the CCUS exam to be utilized on admission in intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…This study has demonstrated that it is feasible to complete the CCUS exam on ICU admission with in a short period (less than 30 minutes) to add more valuable information about the patient besides clinical characteristics, lab work, and other imaging exams. In the consideration of properties of noninvasive, responsible, rapid, affordable and reproducible data collecting at the bedside and providing specific data that may not be obtained from other diagnostic methods[ 33 ], we believe it is precious to encourage the CCUS exam to be utilized on admission in intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Critical care ultrasound has been widely used as a reliable tool in a whole setting of critical care practice [ 1 3 , 48 , 75 ]. As noninvasive, visible point of care handling both monitoring and diagnosis, it has the advantages that any other single tool can not have [ 48 ]. In an intensivist's hand, critical care ultrasound can not only visualize the organ structure as well as the physiopathological changes but also find out the clues to instruct the diagnosis and source searching.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is supposed to be the first part and is done as two steps, and the first step is the fast and global assessment of the heart (heart glance) and thus identifies cases that need immediate life-saving intervention by intensivists or cardiologist (listed in Table 1 ). It is crucial that such situations be identified as early as possible to facilitate an immediate treatment, where showing the unique advantage of the critical care ultrasound compared to the other tools we have in the ICU [ 48 ]. The second step is assessing the circulatory system in the following order: (1) assessing the IVC, which aims to identify the volume status and fluid responsiveness [ 49 ]; (2) evaluating the right heart to identify the acute right heart dysfunction that may harm the output of left side of the heart or cause a false positive monitoring which may mislead the treatment [ 50 – 54 ]; (3) assessing the function of diastole and systole of left heart; (4) deducing systemic vascular resistance.…”
Section: The Piepear Workflow: a Critical Care Ultrasound Based 7-mentioning
confidence: 99%
“…Cardiac ultrasound is more often being used and can indeed be considered as the gold standard and the 'modern stethoscope' for the intensivist. Antoine VieillardBaron and Daniel Lichtenstein, experts in their field, give us their ten best reasons to perform cardiac [51] and lung [52] ultrasound in this issue of AIT.…”
Section: Haemodynamic Monitoringmentioning
confidence: 99%